Royal Jelly and Aliskiren mutually annul their protective effects against gentamicin-induced nephrotoxicity in rats - Mohd Alaraj (Veterinary World, 2020)
Background and Aim: Gentamicin (GM) is one of the most effective antibiotics for severe, life-threatening Gram-negative infections. Nevertheless, its clinical use has been restrained because of its nephrotoxic potential. Royal jelly (RJ) and aliskiren (ALK) can individually prevent such toxic effects. The aim of this study was to explore the protective effects of a combination treatment of RJ and ALK on GM-mediated nephrotoxicity.